Living Group Mosaic Family: participation of people with disabilities in the community - Marta Aoki; Fátima Correa Oliver; Ariane Bazarin de Campos Cancegliero; Júlia Colussi (O Mundo da Saúde)
This is a study on monitoring by a support group for people with disabilities (PWD), performed as a rehabilitation strategy within the territory covered by a Basic Health Unit. The aims of the study are: to reflect on the necessary support for the maintenance of these people in community activities, to identify the main issues presented in group dynamics regarding communication, interpersonal relationships, individual and collective transformations, and to understand current challenges to integrate material production to the Living Group to solidarity economy circuits. The study was developed by means of systematic observations of twenty meetings registered in field reports. 21 people having and not having disabilities took part in the group: 6 having physical disabilities, 7 having intellectual disabilities, 1 having hearing impairment, 2 having multiple disabilities, 01 person in psychological distress and 4 caregivers having unspecific limitations. The study highlighted the challenges for promoting the participation of people having disabilities, as well as to deal with the lack of autonomy and agency of individuals to participate in activities. Joining the group promoted emotional changes, discoveries of skills, promotion of care and learning, self-esteem and communication improvement among participants. Integrating solidarity economy circuits has been one of the group’s challenges, especially considering the lack of accessibility in the city, as well as the inherent difficulties in the marketing of crafted products. It is believed that living groups may be an alternative strategy to promote the participation of PWD in the community.